Closing the Knowing–Doing Gap in Invasive Plant Management: Accessibility and Interdisciplinarity of Scientific Research. Issue 3 (27th June 2013) - Matzek, Virginia; Covino, Justin; Funk, Jennifer L.; Saunders, Martin
Abstract Like many conservation disciplines, invasion biology may suffer from a knowing–doing gap, where scientific research fails to inform management actions. We surveyed California resource managers to evaluate engagement with scientific research and to identify research priorities. We examined managers' access to information, judgment of the usefulness of existing research, ability to generate scientific information, and priorities for future research. We found that practitioners rely on their own experience, and largely do not read the peer‐reviewed literature, which they regard as only moderately useful. Less than half of managers who do research carry out experiments conforming to the norms of hypothesis testing, and their results are not broadly disseminated. Managers' research needs are not restricted to applied science, or even basic ecology, but include social science questions. Scientists studying invasions can make their research more useful by crossing disciplinary boundaries, sourcing research questions from practitioners, and reporting results in accessible venues.